Interactions of antioxidant defense mechanisms developed by plants and microorganisms against pesticides - Karabulut, Fadime; Aydın, Sevinç; Parray, Javid (Micro Environer, 2021)
In the developing world and increasing human population, great importance is given to food security and crop cultivation in climate change. Therefore, different strategies are needed to maintain and revive the crop resources required for agriculture. Pesticides in soil solution can either be adsorbed by soil colloids or degraded by microorganisms. The use of pesticides against diseases and pests that reduce the yield of plants continues to increase day by day. However, it also threatens the life of living things. Over time, many insects and weeds resistant to pesticides have emerged, and it has been seen that the dose of pesticides should be increased. This situation harms both the environment and the economy. Pesticides stay in the soil for many years, preventing microorganism activities and causing oxidative stress induction. Besides, it is known that pesticides inhibit enzyme activities by participating in some enzymatic events. In this review, we discussed the antioxidant defense mechanisms that develop in microorganisms due to the effect of pesticides on microorganisms and provide biodegradation. When exposed to pesticide toxicity in microorganisms that provide biodegradation, specific biological systems characterized by enzymatic reactions become active. In cases where the enzyme defense of microorganisms is insufficient, biotransformation is carried out by artificially supplementing the environment with enzymes; It contains a series of enzyme-catalyzed reactions, and in this way, the negative factors that the plant is exposed to can be eliminated or mitigated. Microbial enzymes provide biodegradation. In addition, to prevent the biodegradation effect; It is essential to examine this subject to improve the understanding and practical use of enzyme use, enzyme extraction methods and future enzyme-assisted bioremediation processes for their development and evaluation.